The insulin-like growth factor (IGF)-I E-peptides are required for isoform-specific gene expression and muscle hypertrophy after local IGF-I production - Barton, Elisabeth R. (American Physiological Society, 2010)
Insulin-like growth factor I (IGF-I) coordinates proliferation and differentiation in a wide variety of cell types. The igf1 gene not only produces IGF-I, but also generates multiple carboxy-terminal extensions, the E-peptides, through alternative splicing leading to different isoforms. It is not known if the IGF-I isoforms share a common pathway for their actions, or if there are specific actions of each protein. Viral administration of murine IGF-IA, IGF-IB, and mature IGF, which lacked an E-peptide extension, was utilized to identify IGF-I isoform-specific responsive genes in muscles of young growing mice. Microarray analysis revealed responses that were driven by increased IGF-I regardless of the presence of E-peptide, such as Bcl-XL. In contrast, distinct expression patterns were observed after viral delivery of IGF-IA or IGF-IB, which included matrix metalloproteinase 13 (MMP13). Expression of Bcl-XL was prevented when viral administration of the IGF-I isoforms was performed into muscles of MKR mice, which lack functional IGF-I receptors on the muscle fibers. However, MMP13 expression persisted under the same conditions after viral injection of IGF-IB. At 4 mo after viral delivery, expression of IGF-IA or IGF-IB promoted muscle hypertrophy, but viral delivery of mature IGF-I failed to increase muscle mass. These studies provide evidence that local production of IGF-I requires the E-peptides to drive hypertrophy in growing muscle and that both common and unique pathways exist for the IGF-I isoforms to promote biological effects.